Software to analyze ETo. Compilation of indirect methods. (August 2021) - Gutierrez-Ninahuaman, Cesar; Gonzalez-Herrera, Roger
Abstract: The present work introduces a computational tool, PETP V2.0.0, which allows calculation and analysis of reference evapotranspiration through empirical formulas from: Thornthwaite, Hargreaves, Christiansen, Penman Monteith, Penman modiﬁed, Turc, Jensen-Haise, Stephens-Stewart, Linacre, Papadakis, Blaney and Criddle, Serruto, Priestley-Taylor, Makkink, Valiantzas, Garcia-Lopez, Turc (annual), Coutagne (annual), and Radiation. In addition, the software has tools for the analysis of ETo (selection of the best results for the study site) and export of results, among others, which are explained in detail in this paper. PETP V2.0.0 has been developed using the Basic programming language, under the Integrated Development Environment Visual Studio 2010, which allows to synthesize manual labor, as it allows to carry out calculations in an automatic and accurate way under different calculation conditions. The ETo parameter is important in calculating water demand, carry out hydrological studies, environmental studies and others, which is why this new computational tool is implemented. Graphical abstract: Image 1 Highlights: This paper reports on a computer program and interface to compute and analize ETo applying different calculation methods. This new computational tool is aimed for use in academic situations and professional works. PETP 2.0.0 was compared to other software obtaining similar results. PETP V2.0.0 has been tested in various regions in Latin America.